Constituents of Aegle marmelos from Myanmar. Issue 9 (2nd September 2021) - Aung, Hnin Thanda; Zar, Thu; Sein, Myint Myint; Komori, Yumiko; Vidari, Giovanni; Takaya, Yoshiaki
Abstract: Five compounds (1 –5 ), including three coumarins (1 –3 ) and two alkaloids (4, 5 ) were isolated during the first investigation of the stem bark of Aegle marmelos (L.) Corrêa. collected in Myanmar. Their structures were determined by NMR spectra analysis. Among them, 7´- O -ethylmarmin (1 ) and 2- O -ethyltembamide (5 ) were identified as new compounds. Skimmianine (4 ) showed moderate cytotoxicity against a HeLa cell line, and 7´- O -ethylmarmin (1 ), marmin (2 ), and (+)-epoxyaurapten (3 ) displayed weak radical scavenging activity according to a DPPH scavenging assay. Graphical abstract: UF0001